Rohingya Muslim Ethnicity: History and Future Dilemma Islam in Myanmar - Muchsin, Misri A.; Armi, Fadhlur (Hikmah, 2024)
Islam entered Myanmar in 1055 AD through Arab traders, initially flourishing in Arakan, which became the centre of the Muslim Kingdom for 350 years. After Arakan was conquered by Burma - later Myanmar - the development of Islam slowed down due to political instability and rejection of Islam by Myanmar's military government as well as provocation from the Israeli government. This research uses a qualitative method with Golchock's historical approach and finds that Rohingya Muslims, ethnic Muslims from Arakan, have been abused by the Myanmar government and Theravada Buddhists for the past 20 years. Hostility towards the Rohingya is due to historical resentment over their 350-year rule and claims that they are illegal immigrants from Bangladesh. The genocide committed by the Myanmar government and Theravada Buddhists since 1982, reaching its peak between 2012-2017, led to a mass exodus of Rohingya to neighbouring countries, especially Bangladesh, where they faced difficult living conditions and chose to leave UNHCR refugee camps. This research highlights the impact of historical conflicts on the Rohingya community, demonstrating the need for a deeper understanding of the political backdrop to address the injustices they experience.